RANCANG BANGUN KONSTRUKSI PANEL SURYA MENGGUNAKAN REFLEKTOR (CERMIN) DENGAN PENAMBAHAN SISTEM PENDINGIN HEATSINK - Ilham Dani (2021)
So far, solar panels have only been known to produce limited electrical energy because they depend on the intensity of light from the sun, the addition of a reflector needed to increase the intensity of sunlight on the solar panel, the addition of a heatsink needed to neutralize the temperature of the panel when reflected sunlight from two reflectors at once that can causes an increase in the temperature of the panel, due to the limited capability of the panel, it is necessary to add a reflector along with a heatsink and equipped with a frame so that the resulting panel product uses a reflector with a heatsink cooling system. heatsink cooling, this is based so that later on we can independently manufacture solar panels using reflectors with a heatsink cooling system, the manufacturing process applied to solar panels uses reflectors with The heatsink cooling system is carried out by applying manufacturing analysis such as the parameters of the cost of making the product, the duration needed to manufacture the product, as well as what kind of processes are needed for the manufacture of the product.